Vegetation misclassification compromises conservation of biodiversity and ecosystem services in Atlantic Forest ironstone outcrops - Silveira, Fernando A.O.; Perillo, Lucas N.; Carmo, Flávio F.; Kamino, Luciana H.Y.; Mota, Nara F.O.; Viana, Pedro L.; Carmo, Felipe F.; Ranieri, Bernardo D.; Ferreira, Matteus C.; Vial, Lígia; Alvarenga, Luciano J.; Santos, Fernando M.G. (Perspectives in ecology and conservation, 2020)
[Display omitted] •Changes in Brazil's legislation threaten conservation of ironstone campos rupestres.•There is no ecological equivalence between ironstone and quartzite campos rupestres.•Specific offset methods are needed to avoid the destruction of ironstone ecosystems. A recent state provision allows quarzitic campo rupestre (QCR) set-asides as in-kind compensation for ironstone campo rupestre (ICR) suppression in the Atlantic Forest, which induces out-of-kind compensation. However, the recently published state provision defines no clear parameters to demonstrate “ecological equivalence” as an in-kind compensation. We evaluated whether there is ecological equivalence between and ICR and QCR in the Brazilian Atlantic Forest. We show marked geological, pedological, floristic, structural, and functional differences between ICR and QCR. There is evidence that the new compensation rules only partially offset loss of biodiversity and ecosystem services hosted by ICR, determining limited effectiveness of the legislation for ICR conservation in the Atlantic Forest. We conclude that the development of clear compensation parameters based on scientific evidence and quantitative indicators is a priority gap for the conservation of ICR under increasing mining pressure.